Glutaredoxin 5 deficiency causes sideroblastic anemia by specifically impairing heme biosynthesis and depleting cytosolic iron in human erythroblasts - Hong Ye; Suh Young Jeong; Manik C. Ghosh; Gennadiy Kovtunovych; Laura Silvestri; Danilo Ortillo; Naoya Uchida; John Tisdale; Clara Camaschella; Tracey A. Rouault (The Journal of Clinical Investigation, 2010)
Glutaredoxin 5 (GLRX5) deficiency has previously been identified as a cause of anemia in a zebrafish model and of sideroblastic anemia in a human patient. Here we report that GLRX5 is essential for iron-sulfur cluster biosynthesis and the maintenance of normal mitochondrial and cytosolic iron homeostasis in human cells. GLRX5, a mitochondrial protein that is highly expressed in erythroid cells, can homodimerize and assemble [2Fe-2S] in vitro. In GLRX5-deficient cells, [Fe-S] cluster biosynthesis was impaired, the iron-responsive element–binding (IRE-binding) activity of iron regulatory protein 1 (IRP1) was activated, and increased IRP2 levels, indicative of relative cytosolic iron depletion, were observed together with mitochondrial iron overload. Rescue of patient fibroblasts with the WT GLRX5 gene by transfection or viral transduction reversed a slow growth phenotype, reversed the mitochondrial iron overload, and increased aconitase activity. Decreased aminolevulinate δ, synthase 2 (ALAS2) levels attributable to IRP-mediated translational repression were observed in erythroid cells in which GLRX5 expression had been downregulated using siRNA along with marked reduction in ferrochelatase levels and increased ferroportin expression. Erythroblasts express both IRP-repressible ALAS2 and non-IRP–repressible ferroportin 1b. The unique combination of IRP targets likely accounts for the tissue-specific phenotype of human GLRX5 deficiency.